Death in the latin quarter - Cardetti, Raphaël, 1972- (Abacus, 2011)
Early one morning among the magnificent honey-coloured buildings of the Sorbonne, the tranquillity of the university is shattered by a death.But why would Albert Cadas, a quiet, crumpled professor of medieval literature, have any reason to kill himself?Meanwhile in another part of Paris, Valentine Savi, a talented young restorer, receives a visit in her studio from an enigmatic elderly gentleman with a unique commission:to restore a priceless medieval palimpsest whose timeworn pages promise to reveal the truth of a mystery that has fascinated scholars and writers for hundreds of years.Valentine soon learns that the shadowy figures who seek to possess the secrets of the manuscript are far darker and more ruthless than she could ever have imagined...Together with her friend Hugo Vermeer -- aristocrat, epicure and incorrigible wheeler-dealer -- and David Scotto, Cadas's doctoral student, Valentine finds herself on a terrifying and thrilling adventure through the narrow streets and gloomily palatial mansions of the Latin Quarter.